Security Challenges of the Internet of Things - Samaila, Musa Gwani (2020)
The Internet of Things (IoT) is an environment in which ordinary and complex consumer products, buildings, bridges, animals or even people, etc. are embedded with sensors, equipped with a variety of communication technologies and given unique identifiers that can enable them connect to the Internet. This allows them to talk to each other, collect data and transfer data over the Internet. IoT has the potential to enhance the way we do things by increasing productivity and efficiency. It also has the prospects of delivering significant business benefits. Nonetheless, implementing secure communication in the IoT and integrating security mechanisms into some of its devices have been a major impediment to its progress, resulting in many privacy concerns. Although IoT is a hybrid network of the Internet, many security solutions for the Internet cannot be directly used on the resource-constrained devices of the IoT, hence the need for new security solutions. In this chapter, we discuss the security challenges of the IoT. First, we discuss some basic concepts of security and security requirements in the context of IoT. We then consider fundamental security issues in the IoT and thereafter highlight the security issues that need immediate attention.